Draft Genome Sequences of Six Novel Bacterial Isolates from Chicken Ceca - Duggett, Nicholas A.; Kay, Gemma L.; Sergeant, Martin J.; Bedford, Michael; Constantinidou, Chrystala I.; Penn, Charles W.; Millard, Andrew D.; Pallen, Mark J. (Genome announcements (Washington, DC), 2016)
The chicken is the most common domesticated animal and the most abundant bird in the world. However, the chicken gut is home to many previously uncharacterized bacterial taxa. Here, we report draft genome sequences from six bacterial isolates from chicken ceca, all of which fall outside any named species.